(3OhQ GdehGQO GdHTQjI aj Jehjd GdJfejI (B:s (3Hjf GdfXGe GdeGdi GdGSdGei hGdfXGe GdeGdi GdhVYi (B/s - (3GdLed, gTGe eUWais ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2007)
(3GdScGf hGdJfejI Hjf GdfXGe GdeGdj GdGSdGej hGdfXGe GdeGdj GdhVYj(B: (3eGgjI GdJfejI hebheGJgG hCgOGagG, Gdfeh GdScGfj GdYGdej hVhGHWg, GdJfejI GdGbJUGOjI hGdGLJeGYjI ddehGQO GdHTQjI(B: (3GdJfejI GdGbJUGOjI ddehGQO GdHTQjI Hjf GdfXGe GdeGdj GdGSdGej hGdfXGe GdeGdj GdhVYj, GdJfejI GdGLJeGYjI ddehGQO GdHTQjI Hjf GdfXGe GdeGdj GdGSdGej hGdfXGe GdhVYjs
(3HHdjhZQGajG(B: (3U(B.519s
Keywords: (3GdJehjds; (3GdJfejI GdGbJUGOjIs; (3Gdbhi GdYGedIs